Protocol for a clinical trial of telehealth-based social communication skills training for people with traumatic brain injury and their communication partners. Issue 1 (29th March 2020) - Rietdijk, Rachael; Power, Emma; Brunner, Melissa; Togher, Leanne
Abstract: Background: A previous clinical trial of training communication partners of people with traumatic brain injury (TBI) demonstrated positive outcomes [Togher, Power, McDonald, Tate, & Rietdijk (2009). Brain Impairment, 10(2), 188-204]. Adapting communication partner training for delivery via telehealth could improve access to this intervention. Objectives: To compare outcomes across in-person communication partner training, telehealth communication partner training and a control group Method: Protocol for a partially randomised controlled trial. People with moderate-severe TBI will be allocated to either an in-person or telehealth-based training program. Comparison data will be drawn from the original trial control group, which was recruited using the same eligibility criteria as this protocol. Outcomes after training will be compared between the in-person training group, the telehealth training group and the historical control group. Discussion: This protocol uses specific design features with the aim of maximising the study's power, including a partially randomised allocation process and a historical control group. The results will inform about the feasibility and effectiveness of delivering TBI rehabilitation via telehealth. Trial registration: Australian and New Zealand Clinical Trials Registry: ACTRN12615001024538.